THE AUTHORITY OF ADMINISTRATIVE COURTS IN VILLAGE HEAD ELECTION DISPUTES - Wahyudin, Wahyudin; Afiyah, Siti; Bagus, Salahudin Serba; Sundari, Ariefah (EQUALEGUM International Law Journal, 2025)
Background. Although village elections are inherently political, they also entail administrative dimensions subject to legal scrutiny, particularly regarding the regent’s decree confirming election results. The absence of a consistent legal interpretation has generated uncertainty within administrative judicial practice. This study examines the jurisdictional authority of the State Administrative Court (PTUN) in adjudicating village head election disputes, using the case of Ngarum Village, Lamongan Regency, as a focal point. Research Method. Employing a normative-empirical legal approach, this study integrates doctrinal analysis of administrative law and statutory frameworks with empirical observations of PTUN Surabaya’s handling of election disputes. Findings. The research identifies significant judicial inconsistency across PTUN jurisdictions in classifying regents’ decrees; some deem them political acts, while others recognize them as administrative decisions open to judicial review. Such divergence undermines legal certainty and equitable access to justice. Conclusion. PTUN possesses legitimate authority when a regent’s decree fulfills the characteristics of an administrative decision. Institutional reinforcement and uniform judicial guidelines are imperative to enhance accountability, ensure procedural fairness, and strengthen democratic governance at the local level.